Latvijas nebanku finanšu sektora attīstības tendences un nozīme tautsaimniecībā - Miķelsons, Elvis (Latvijas Universitāte, 2019)
Bakalaura darba tēma ir „Latvijas nebanku finanšu sektora attīstības tendences un nozīme tautsaimniecībā‖. Nebanku finanšu sektora attīstība spēlē ļoti lielu lomu tautsaimniecības attīstībā, tādēļ autors izrādīja vēlmi aplūkot šī sektora dalībniekus, to nozīmi Latvijas tautsaimniecības attīstībā gan vēsturiski, gan šobrīd. Darbā tiek analizēts pašreizējais nebanku finanšu sektora dalībnieku sastāvs, to funkcijas, un to attīstība Latvijā no 2013.gada līdz 2018.gadam. Darba saturs ir izklāstīts trīs nodaļās. Pirmajā darba daļā autors analizē iegūto informāciju par nebanku finanšu sektora dalībniekiem, to būtību un funkcijām. Otrajā darba daļā tiek analizēti nebanku finanšu sektora dalībnieki laikaposmā no 2013. līdz 2018.gadam. Trešajā daļā autors veic anketēšanas rezultātu apkopošanu un analīzi. Darba nobeigumā tika veikti secinājumi un priekšlikumi nebanku finanšu sektora attīstības uzlabošanai. Izstrādātais darbs ir veikts uz 66 lapaspusēm, satur 37 attēlus un 9 tabulas.

The subject of the bachelor's thesis is "Development tendencies and significance of Latvian non-bank financial sector in the national economy". The development of the nonbank financial sector plays a very important role in the development of the national economy, therefore the author expressed a desire to look at the participants of this sector, their role in the development of the Latvian economy both historically and now. The thesis analyzes the current composition of non-bank financial sector participants, their functions and their development in Latvia from 2013 to 2018. The contents of the work are presented in three chapters. In the first part of the work, the author analyzes the information obtained about nonbank financial sector participants, their nature and functions. The second part of the work analyzes non-bank financial sector participants from 2013 to 2018. In the third part, the author summarizes and analyzes the results of the questionnaire. At the end of the work, conclusions and suggestions were made to improve the development of the non-bank financial sector. The developed work has been carried out on 66 pages, contains 37 images and 9 tables.
Development tendencies and significance of Latvian non-bank financial sector in the national economy
Keywords: Ekonomika; Nebanka; Kredītdevējs; Finanšu sektors; Tautsaimniecība